Aplicação da eletrocoagulação assistida por radicais livres na remoção de p-nitrofenol em solução aquosa - Pereira, Thiago Castanho (2020)
The p-nitrophenol (PNP) is a hazardous nitroaromatic synthetic compound, with mutagenic and recalcitrant characteristics in environmental compartments. The electrocoagulation processes (EC) have arisen as an efficient method for hazardous pollutant removal. As a result of sacrificial anodes dissolution and cathodic water reduction, coagulant species are formed in situ leading to charge neutralization and pollutant adsorption in the formed coagulant. Coupling EC with chemical oxidants like sodium persulfate can increase the removal of toxic and recalcitrant pollutants in aqueous solution. In this issue, the present work aimed to optimize the EC process for PNP removal in aqueous solution. The process was carried out in a 15 L cylindrical air-lift reactor with internal recirculation using four aluminum or iron electrodes in monopolar arrangement connected to a DC power supply. For this optimization, a 2³ factorial experimental design was performed to evaluate the effects of the initial pH (pHi), current density (j), and concentration of PNP (CPNF), having as response variable the efficiency of PNP removal and soluble metal residual concentration after 10800 s of treatment. For the optimal condition with Fe electrodes experiments were carried out with the addition of sodium persulfate (PS) in different concentrations (2380.8, 1190.3, 476.1 mg L-1). The effect of SP was verified in the presence of electrical current (EC + PS) and in its absence (Fe0 + PS). For the experiments with oxidizing agents, the effect of bicarbonate anion was verified in the process. For EC process was verified the adjust of data to a first-order kinetic model. PNP removal meeting environmental standards of Al e Fe discharges in wastewater was verified in pHi = 5.22, j = 8.06 mA cm-2 and CPNF = 14.12 mg L-1, for both electrodes. For Al electrodes maximum removal efficiency observed was 61% (k = 8,43(0,19)10-5 s-1), and 69% (k = 10.28(0.36)10-5 s-1) for Fe electrodes in 10800 s of reaction. For PS experiments it was observed PNP degradation even in the absence of electrical current between electrodes, due to PS heterogeneous activation. In a PS concentration of 2380.8 mg L- 1 was achieved kinetic constants k = 7.56(0.24)10-4 s-1 for Fe0 + PS process, and k = 7.88(0.28)10-4 s-1 for EC + PS process. PS presence in EC process led to an 81% less electrical energy consumption in the process. Results showed better advantages for Fe electrodes utilization, due to its higher removal efficiencies and higher environmental compatibility.